2004
DOI: 10.1172/jci200422186
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of cholesterol homeostasis by plant sterols

Abstract: The ABC transporters ABCG5 and ABCG8 limit absorption and promote excretion of dietary plant sterols. It is not known why plant sterols are so assiduously excluded from the body. Here we show that accumulation of plant sterols in mice lacking ABCG5 and ABCG8 (G5G8 -/-mice) profoundly perturbs cholesterol homeostasis in the adrenal gland. The adrenal glands of the G5G8 -/-mice were grossly abnormal in appearance (brown, not white) due to a 91% reduction in cholesterol content. Despite the very low cholesterol l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 51 publications
3
62
2
1
Order By: Relevance
“…Surprisingly in this context, expression of the gene encoding 3-hydroxy-3-methylglutaryl-CoA reductase was not affected in megakaryocytes from Abcg5 Ϫ/Ϫ mice, suggesting that cellular cholesterol synthesis was unchanged. High plant sterol levels have previously been reported to be associated with increased Abca1 expression in adrenal glands in Abcg5 Ϫ/Ϫ /Abcg8 Ϫ/Ϫ double knock-out mice due to activation of the liver X receptor (45). However, this clearly does not happen in megakaryocytes, indicating that cholesterol homeostasis is differentially affected by plant sterols in different cell types.…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly in this context, expression of the gene encoding 3-hydroxy-3-methylglutaryl-CoA reductase was not affected in megakaryocytes from Abcg5 Ϫ/Ϫ mice, suggesting that cellular cholesterol synthesis was unchanged. High plant sterol levels have previously been reported to be associated with increased Abca1 expression in adrenal glands in Abcg5 Ϫ/Ϫ /Abcg8 Ϫ/Ϫ double knock-out mice due to activation of the liver X receptor (45). However, this clearly does not happen in megakaryocytes, indicating that cholesterol homeostasis is differentially affected by plant sterols in different cell types.…”
Section: Discussionmentioning
confidence: 98%
“…However, the mechanism by which serum cholesterol levels increase during breastfeeding in sitosterolaemia is still unclear. Stigmasterol, the other plant sterol that accumulates in sitosterolaemia, inhibits the processing of a transcription factor, sterol regulatory element binding protein-2 which stimulates the transcription of hepatic LDLR (Yang et al 2004). Accordingly, the transcription of hepatic LDLR is assumed to be inhibited, resulting in an increase in circulatory cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…This observation indicates that sitosterol might possess a cell-proliferating or cell-protecting property which overcomes ER stress and the proposed cytotoxic effect of free sterol accumulation. A previous study which analyzed differential effects among different sterols on cholesterol homeostasis in adrenal cell line Y1-BS1 cells has shown that sitosterol had less potency in the processing of SREBP-2 than cholesterol, leading to less potent suppression of HMG-CoA reductase in these cells 33) ; thus it is probable that a slight but distinct difference in the chemical structure among sterols leads to a difference in the plasticity of cell membranes, causing differential effects on cell proliferation or viability. Future studies are awaited to clarify this mechanism.…”
Section: Discussionmentioning
confidence: 99%